Cost-effective polymer-based membranes for drinking water purification. (June 2022) - Xu, Xiaohan; Yang, Yuqing; Liu, Tianbo; Chu, Benjamin
Abstract: Global water scarcity is exacerbating owing to climate change and pollution, making the demand for clean water more challenging with the growth of the global economy and population. Membrane filtration technologies have been widely applied in drinking water purification due to their energy efficiency while facing challenges like fouling, degradation and trade-offs, such as selectivity and permeability. The sustainable development of our society demands further understanding and improvement of those membranes. In this review, the basic structures of polymer-based water purification membranes including the effective layer for separation, the support layer and the possible top protective layer are presented. Details include the conventional membranes for microfiltration (MF) and ultrafiltration (UF), the effective layers for separation in thin-film composite (TFC) membranes, electrospun nanofibrous membranes for MF, UF, and membrane distillation (MD), as well as the emerging self-assembled block copolymer membranes. Furthermore, the conventional support layers and electrospun nanofibrous support layers for reverse osmosis (RO) and forward osmosis (FO) processes, and the top protective layers are discussed. The materials, membrane structures and properties, modification strategies, possible interlayers, interconnects, interpenetration, and interactions between different layers are discussed, with the emphasis on the cost-effectiveness of various membranes. Graphical abstract: Image, graphical abstract .